Sputum without error: Nursing conducts for quality collection na contamination prevention (Research, Society and Development, 2025)
The aim of this study was to analyze scientific evidence on nursing practices in sputum collection for the diagnosis of respiratory diseases, particularly pulmonary tuberculosis, identifying strategies that ensure sample quality and prevent contamination. This is an integrative review conducted according to PRISMA 2020, including ten studies published between 2020 and 2025. The findings show that sample quality depends directly on adequate patient guidance, proper use of Personal Protective Equipment (PPE), technical supervision, and strict adherence to biosafety procedures. The most frequent errors include collecting saliva instead of lower airway secretions, mishandling of the container, and delayed transport, which compromise diagnostic accuracy and increase biological risk. The literature highlights that technique standardization, continuous professional training, sputum induction when necessary, and the use of institutional protocols significantly reduce contamination, improve nursing performance, and enhance microbiological reliability. It is concluded that nursing plays a decisive role in diagnostic accuracy and in strengthening respiratory infection control actions, especially within tuberculosis surveillance programs.